Beyond flirtation: social sexual behavior and employee innovation — the moderating effects of gender and social sexual behavior frequency - Jang, Eunmi (Frontiers in Psychology, 2025)
This study examines how supervisors’ social sexual behavior (SSB) affects subordinates’ psychological social resources and innovative behavior, focusing on the moderating effects of gender and SSB frequency. Survey data from 212 employees in South Korean private sector organizations indicate that positive perceptions of supervisors’ SSB enhance subordinates’ psychological social resources, which in turn promote innovative behavior. Gender moderates the relationship between SSB and psychological social resources, with female employees experiencing stronger positive effects than males. However, high frequency of SSB weakens this positive effect, suggesting an optimal level of such behavior. These findings advance the literature on workplace SSB by demonstrating its potential to foster innovation through psychological resources while highlighting individual and contextual differences. Implications for organizations include fostering innovation-supportive environments that respect appropriate interpersonal boundaries.